Ethyl methanesulfonate mutant library construction in Neopyropia yezoensis to provide germplasm resources for next-generation genome-selection breeding - Kong, Fanna; Yin, Jiqiang; Yu, Xinzi; Wang, Junhao; Sun, Bin; Mao, Yunxiang; Kim, Jang Kyun; Ren, Hongzhong; Yue, Huijie; Yu, Chenggong; Miao, Xinping; Sun, Ying (Frontiers in Marine Science, 2023)
With the development of the laver industry, germplasm depression has become a serious issue, and current cultivars cannot adapt to different aquaculture regions. In order to increasing the genetic diversity and developing more germplasm sources, it is urgent and reasonable to construct a mutant library with more new germplasms. In this research, a mutant library was constructed by ethyl methanesulfonate (EMS)-mutagenized archeospores, and the most optimal treatment procedure was determined by performing different mutagen concentrations (2.25%) and treatment times (30 min). A total of 1860 haploid thalli were produced as the M1 mutant population and further cultured into conchocelis clones for the reservation of germplasm resources. Among these, 667 individual thalli were evaluated for their phenotypic traits, including thallus length, thallus width, length/width, thallus shape, photosynthesis ability, thallus color, thallus margin, and specific growth speed. The mutation frequency of the length/width ratio was 17.39%, Fv/Fm and NPQ were 21.84% and 29.35%, respectively, and SGR was 13.59%. The mutation frequency of thallus color was 0.91%. This work may not only provide a basic practical reference guide for EMS-based mutant library construction for other seaweeds but, more importantly, also serve as a valuable resource for functional genomics research and laver breeding.